STUDY PEMODELAN IMPAK PADA PANEL BAHAN KOMPOSIT DENGAN METODE ELEMEN HINGGA - Saputra, Hadi; Rochardjo, Heru Santoso Budi (Lembaga Penelitian & Pengabdian Kepada Masyarakat (LPPM), IST AKPRIND Yogyakarta, 2011)
Generally manufacturing of composite materials is performed using trial and error method.The finite element method show the capability to optimize that process.The efficient formulation for simulating high speed impact usually uses explicit dynamic method. The purpose of this research is modelling impact loading on composite panel using finite element method as a part of preprototyping impact resistant composite material.The process of impact simulation on composite panel using explicit dynamic formulation can be done using commercial application software, that done with variation on impactor velocity (200, 400, 600, 800, 900, and 1000m/s), impactor geometry likes cone and blunt, Elasticity modully of lamina composite materials, the direction of fiber as symmetric cross plies and symmetric angle plies, and the thickness, 4, 6, 10 plies.The result showed that impact simulation on composite panel using this software can be performed well, the influence of impactor velocity shows increased the Von Misses Stress with average value 2.41% (in 200-400m/s), 1.59% (in 400-600m/s), 1.28% (in 600-800 m/s), 1.20% (in 800-1000m/s). Cone A type with the smallest area of contact have the best capability to penetrated compared with B type and blunt type. Symmetric angle plies have better impact resistant compared with symmetric cross plies.